Diversity, ecology, distribution and biogeography of Diplura. Issue 4 (18th March 2021) - Sendra, Alberto; Jiménez‐Valverde, Alberto; Selfa, Jesús; Reboleira, Ana Sofia P. S.
Abstract: Diplura is the sister group to insects and one of the three basal hexapod groups with unique entognathan mouthparts. The order is divided into 10 families, which include 1008 species in 141 genera, with a high proportion of monotypic genera. They are ubiquitous in soils and subsurface terrestrial habitats, as well as have an important role in overall biogeochemical cycles. We present the first comprehensive review of the global biodiversity and ecology of Diplura. We highlight four aspects of this basal hexapod group: diversity in morphological body plans and sizes; ecology in terrestrial environments from soil to caves; food preference and trophic levels, and their biogeographical and paleobiogeographical significance. Diplura depends on high humidity and moderate temperatures. They are presumably very sensitive to anthropogenic pressures and climate change, and therefore are a suitable model for ecophysiological studies and evident priority targets for conservation. We conclude that the future efforts should focus on establishing a molecular phylogeny to clarify the relationships between and within families, as well as to reveal global biogeographical patterns. This will require an increase in sampling effort in several regions of the globe, especially in tropical regions. Abstract : Diplura is the sister group to insects. The order is divided into 10 families, which include 1009 species in 141 genera, with a high proportion of monotypic genera. Diplura depends on high humidity and moderate temperatures, are presumably very sensitive to anthropogenic pressures and climate change, and a suitable model for ecophysiological studies and priority targets for conservation. Future efforts should focus on establishing a molecular phylogeny to clarify the relationships between and within families, as well as to reveal global biogeographical patterns.